Physical Activity Is Associated With Improved Eating Habits During the COVID-19 Pandemic - Christofaro, Diego G. D.; Werneck, André O.; Tebar, William R.; Lofrano-Prado, Mara C.; Botero, Joao Paulo; Cucato, Gabriel G.; Malik, Neal; Correia, Marilia A.; Ritti-Dias, Raphael M.; Prado, Wagner L. (Frontiers in Psychology, 2021)
The aim of this study was to analyze the association between physical activity and eating habits during the COVID-19 quarantine among Brazilian adults. A sample of 1874 participants answered an online survey. The impact of the COVID-19 pandemic on eating habits was assessed inquiring about participants’ intake of fruits, vegetables, fried foods and sweets during the pandemic. Physical activity was assessed by asking participants about their weekly frequency, number of minutes/hours spent engaging in structured activities per week, and intensity. Respondents were then stratified into categories based on moderate-to-vigorous intensity (0-30; 31-90; 91-150; 151-300; and >300 minutes/week) and into active (≥150 minutes) or inactive (<150 minutes). Increased sweets consumption was the most commonly reported change to eating habits (42.5%), followed by an increase in the consumption of vegetables (26.6%), fruits (25.9%), and fried foods (17.9%). Those identified as physically active modestly increased their fruit consumption (OR= 1.22, p=0.08) and were less likely to increase their consumption of fried foods (OR= 0.57, p<0.001) and sweets (OR= 0.49, p<0.001). A cluster analysis revealed that the higher the level of physical activity, the more likely the participant was to follow a healthy diet (p<0.001). Behaviors during COVID-19 quarantine need to be studied since this is a novel situation and that this research sheds light on behaviors during a pandemic/quarantine The practice of physical activity and improved eating habits during the pandemic could be beneficial to individuals’ overall health.